Oral Immunotherapy Using Probiotic Ice Cream Containing Recombinant Food-Grade Lactococcus lactis Which Inhibited Allergic Responses in a BALB/c Mouse Model - Alireza Vasiee; Fereshteh Falah; Mojtaba Sankian; Farideh Tabatabaei-Yazdi; Seyed Ali Mortazavi (Journal of Immunology Research)
This study was conducted to evaluate the effects of recombinant probiotic bacteria as a candidate for oral vaccine with the potential of treating allergy to Amaranthus retroflexus pollens. The main gene of this allergen, Ama r 2, was cloned into the food grade plasmid pNZ7025 and then was electrotransformed into the food grade Lactococcus lactis NZ1330. No expression was observed in the primary structure due to the distance between the ribosome binding site and the start codon. Therefore, the vector structure was corrected using the site-directed mutagenesis (SDM) technique. The cell extract of this strain was used for assessing the expression of the recombinant allergen in western blot analysis, and the existence of this protein with a molecular weight of 14.2 kDa was confirmed. To evaluate the efficacy of this strain in the treatment of allergies as an oral vaccine, probiotic ice cream was prepared. After the sensitization of mice, the treatment was performed by oral immunotherapy for 4 weeks, 4 to 5 times per week. 20 μl of functional ice cream with 1012 CFU/ml of r-L. lactis NZ1330 significantly reduced the serum IgE level. The levels of IFN-γ and TGF-β cytokines increased in the 20 μl ice cream treatment group as well as 40 μg/ml pure allergen compared with the PBS-treated group, and IL-4 cytokine levels decreased compared with the PBS-treated group. Overall, 20 μl ice cream with 1012 CFU/ml of the recombinant bacteria resulted in the best performance in terms of improving allergies to Th1 and Treg responses.